Konsep Dzikir Sebagai Terapi Gangguan Bipolar - Esya Heryana; Muhsin Mahfudz; Winona Luthfiah; Fitriani Fitriani; Raihan Raihan (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss the concept of dhikr in the Qur'an as mental health therapy for bipolar sufferers by explaining verses related to the concept of dhikr in the Qur'an as a therapy for bipolar disorder. This study uses a descriptive qualitative approach using the thematic interpretation or maudhu'i research method, this method seeks to collect verses from the Qur'an regarding the problems or topics to be discussed and then analyzed so that they will become a unified whole. The results and discussion of this study show the concepts offered by the Qur'an related to dhikr that can be used as a therapy for bipolar disorder which results in an imbalance of mind and soul which states the impact of dhikr to create peace and tranquility of the soul. This study concludes that there is an effect of dhikr that affects the mind and also the heart as mental health therapy for bipolar sufferers, namely with dhikr a person will feel peace and peace in his soul which makes the mind balanced, clear and more focused so that different feelings change automatically. drastic for people with bipolar can be controlled. Peace by remembering Allah swt. will seep into the heart and mind then dhikr not only has an impact on the mind which gives rise to clear thinking but more than that, dhikr also has an impact on the heart which creates peace of mind.